Cost-effectiveness of watchful waiting versus immediate emergency department transfer after epinephrine autoinjector use in Canada - Yiwei Yin; Moshe Ben Shoshan; Marcus Shaker; Matthew Greenhawt; Kate M. Johnson (Allergy, Asthma & Clinical Immunology)
Abstract Background Until recently, immediate emergency department (ED) transfer after food-related anaphylactic reactions was recommended regardless of symptom resolution following use of an epinephrine autoinjector (EAI). We evaluated the cost-effectiveness of delayed ED transfer after EAI use in non-medical settings (watchful waiting) compared to immediate ED transfer among pediatric patients with food allergies in Canada. Methods We developed a probabilistic Markov model of individuals starting at age of one year who are at risk of severe food-related allergic reactions requiring epinephrine. We evaluated medical costs (in 2022 Canadian dollars) and quality-adjusted life years (QALY) of each strategy over a 20-year horizon. In the base case, we assumed a tenfold increase in food allergy fatality for patients under watchful waiting, which we increased to 100- to 1,000-fold in sensitivity analysis. The analysis was conducted from the Canadian healthcare system perspective with a 1.5% annual discount rate and a willingness-to-pay (WTP) threshold of $50,000 per QALY. Results Immediate ED transfer following EAI use resulted in a decreased risk of food allergy fatality of 9.2 × 10− 5 over 20 years, which is equivalent to < 1 fatality per 200,000 patient-years. Watchful waiting resulted in cost savings of $1,157 per patient and a QALY loss of 7.28 × 10− 4; an incremental cost per QALY saved of $1,589,854. The incremental cost per death prevented with immediate ED transfer was $12,586,613. Watchful waiting remained cost-effective in all sensitivity and scenario analyses, except under extreme increases in fatality risk of 500-fold and 1,000-fold. Conclusions Watchful waiting for symptom re-occurrence following EAI administration in non-medical settings is cost-effective.